Electrochemical study of magnesium diboride modified electrode - Yusri, Mohd Farhan (2011)
Use of a glassy carbon (GC) modified by adhered microparticles of MgB2 mediates the reduction process of Fe(CN)6 3- during cyclic voltammetry. Potential at reduction peak was observed to shift slightly from 0.20 to 0.23 V and current is significantly enhanced by about two folds. The sensitivity under conditions of cyclic voltammetry is significantly dependent on pH,electrolyte and scan rate. The result of scanning electron micrograph of MgB2 obtained before and after electrolysis show the size of the MgB2 microparticles increased slightly to the size ranging from 2 - 5.5 μm attributing to the hydration effect and/or incorporation of some ionic species into the crystal lattices of MgB2. Interestingly, redox reaction of Fe(III) solution using modified GC electrode remain constant even after 15 cycle reflecting the usability of the MgB2 film attached to the GC electrode surface. Use of a lithium doped magnesium diboride modified glassy carbon electrode enhance the oxidation current of ascorbic acid during cyclic voltammetry compare to bare GC and MgB2 modified electrode. Peak potential was observed to shift slightly from around 0.40 to 0.25 V and current is significantly enhanced by about two folds. The sensitivity under conditions of cyclic voltammetry is significantly dependent on pH,temperature, electrolyte and scan rate. The result of scanning electron micrograph of MgB2 with Li+ doped obtained before and after electrolysis show the size increased slightly to the size ranging from 0.5 - 1.3 μm to 3 –7 μm attributing to the hydration effect and/or incorporation of some ionic species into the crystal lattices of MgB2. The oxidation current of ascorbic acid decreased sharply after the first cycle and become stable with minor decreases after second cycle. The recovery values of 99.0±0.4% was obtained after the addition of 0.5 mM ascorbic acid into rose flavour syrup while recovery of 99.2±0.1% was obtained after the addition of 0.05 mM ascorbic acid into rose syrup